Comparative Pharmacology of Cefaclor and Cephalexin - Korzeniowski, Oksana M. (1977)
Two cephalosporin antibiotics, cefaclor and cephalexin, were administered orally to healthy, adult male volunteers for comparison of their pharmacological properties. In doses of 250 mg orally, cefaclor produced a peak serum concentration of 6.01 ± 0.55 (standard deviation [SD]) μg/ml compared with 9.43 ± 2.36 μg/ml for cephalexin (P < 0.01). The half-lives were 0.58 ± 0.07 (SD) h and 0.80 ± 0.12 (SD) h, and elimination constants were 1.22 ± 0.15 and 0.88 ± 0.13 h(−1) for cefaclor and cephalexin, respectively (P < 0.001). Neither drug showed accumulation over the dosing period, and both were well tolerated.